Bakti Sosial Pelayanan Kontrasepsi Dalam Rangka Memberdayakan Masyarakat Untuk Menyukseskan Program Keluarga Berencana - Natalia, Shanty; Kusuma K, Ferie; Kotijah, Siti; Sulistyorini, Sulistyorini; Septa D.A, Fira; Agustiningsih, Dwi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Family Planning is an action that helps married couples to avoid unwanted births, regulate birth spacing, and determine the number of children in the family. The use of contraception is a shared responsibility between men and women as a couple, so that the contraceptive method that will be chosen is in accordance with the needs and desires of each other. The method used in this community service activity is to form a forum consisting of women of childbearing age in Manyaran Village, Banyakan District. Objective: The purpose of this activity is to involve husbands by increasing understanding and knowledge. So the purpose of this community service activity is to empower married couples to play an active role in increasing the use of contraceptives. Then with the presentation of material related to family planning to create a healthy generation, and then a questionnaire was given to all participants as an evaluation of whether there was a change in knowledge after being given the material. Method: This community service activity uses the Participatory Action Research (PAR) method by forming a forum consisting of women of childbearing age in Manyaran Village, Banyakan District. The number of participants who attended the activity was 37 people. In this service, before and after counseling, a questionnaire was given (pretest and posttest) to measure the level of knowledge, then social service for contraception services was carried out. Result: there was an increase in knowledge of fertile couples regarding family planning. After participating in the activity, 80% of participants' knowledge was good and 20% were sufficient. This activity provides benefits for participants to plan their families in order to create a healthy generation. Conclusion: The purpose of this activity has been achieved, which is indicated by the smooth running of the activity and the high enthusiasm of the participants in participating in the activity. After this, it is hoped that participants can plan their pregnancies, regulate the spacing of pregnancies in order to create a healthy generation.